Determinants of Fraudulent Financial Reporting with Auditor Quality as A Moderating Variable - Irawan, Helmiansyah; Chinwuko, Fidelia Ifeyinwa Nzekwe (Universitas PGRI Madiun, 2026)
Background;Various models have been developed to explain why financial reporting fraud occurs, with the aim of understanding the elements that trigger unethical actions, starting from the fraud triangle to the Fraud Star Theory.The study aims to test the influence of the independent variables stimulus, capability, collusion, opportunity, rationalization, ego, and lack of whistleblowing system on the dependent variable fraudulent financial statements with the moderating variable being audit quality. (2) Methods;The research data analysis technique uses the moderated multiple regression analysis method (Moderated Regression Analysis/MRA).This study selected all companies listed on the Indonesia Stock Exchange as the research population, considering that these companies have relatively uniform characteristics and financial reporting obligations in accordance with capital market regulations. The sample was selected using a purposive sampling method. (3) Results: based on the test results, it was found that the collusion and ego variables had no influence on financial report fraud, while the other variables had a significant influence and auditor quality could not weaken the relationship. (4) Conclusions;Audit quality was found to weaken the positive effect of stimulus on financial statement fraud. Audit quality was unable to reduce the positive effects of leadership capability, collusion, opportunity, rationalization, ego, and lack of a whistleblowing system on financial statement fraud.